Case Study Of Hemorrhoid Clients With Jamu Government - Ag. Kirwanto; Ronal Tolkhah; Susilo Yulianto (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
Hemorrhoids can be described as a lump of tissue in the anal canal containing blood vessels and surrounding supporting tissue, consisting of muscles and elastic fibers. The purpose of this study was to determine the history, symptoms, management, and development of hemorrhoid patients. The research method used was qualitative with a descriptive research design. The sampling technique was purposive sampling. This study used 2 informants with data collection techniques, namely in-depth interviews, observation, and documentation and a validity test was carried out using the triangulation technique. The results of the study showed that the history of hemorrhoid patients felt painful and sore during bowel movements. Symptoms of hemorrhoid disease consist of hot waist, pain, burning during bowel movements, lumps coming out of the anus during heavy activity, hard stools . Management of hemorrhoid patients involves regulating good food intake, physical exercise has an effect on the healing of hemorrhoid patients, herbal medicine therapy includes capsules and decoctions. The development of hemorrhoid patients using herbal capsules is characterized by defecation not feeling pain and pain is reduced but does not reduce the existing lumps, as well as several effects that appear after taking herbal medicine such as defecating immediately and farting continuously. The conclusion of this study is that there is a development marked by patients not feeling pain when defecating but not reducing the existing lumps.